Using an Isomorphic Instrument: What Do Physics Education Students Think About Buoyance? - Maison; Hidayati; Dwi Agus Kurniawan; Riska Fitriani (Jurnal Penelitian Pendidikan IPA, 2023)
Physics education students' understanding of buoyancy can differ from student to student and is difficult to know accurately. Appropriate instruments are needed to diagnose the conception of physics education students. This research aims to determine how physics education students think about buoyancy by applying a five-tier isomorphic instrument. The respondents of this research were physics education students at Padang State University who had studied Archimedes' principle regarding buoyancy, totaling 135 people. The research results show that physics education students have different average percentages of correct answers regarding the number of tiers. The average percentage of correct answers in the first tier is 13%, while in the combination of tier 1 and tier 3 (two-tier) is 7%. Overall, the average percentage of correct scores based on tiers one to four (four-tier instrument) on the buoyancy concept is 4%. They are, furthermore, based on isomorphic analysis: ISO-1 = 8%, ISO-2 = 1%, and ISO-3 = 8%. These results are then classified as poor conceptual understanding because the percentage of conceptual understanding obtained is below 30%. The source of physics education students' conceptions comes from personal thoughts about 80%, from observations about 15%, and the rest from other sources.